Pengembangan Kompetensi UMKM Kota Jayapura Berkarakter Tecnopreneurship Membuka Segmen Pasar Baru dengan Digital Marketing untuk Memasuki Pasar Global - Onnie Lumintang; Kristina Edowai (Universitas Kristen Indonesia Toraja, 2023)
This article discusses the development of Micro, Small, and Medium Enterprises (MSMEs) competencies in Jayapura City with a technopreneurship approach, which aims to open new market segments through digital marketing. By utilizing digital technology, MSMEs are expected to increase their competitiveness and enter the global market. This study uses qualitative and quantitative methods to analyze the potential and challenges faced by MSMEs in Jayapura. The results of the study indicate that the development of technopreneurship competencies can encourage innovation and expand the marketing network of MSMEs, as well as increase access to international markets.